Progressionsverlauf experimentell ausgelöster arteriosklerotischer Gefäßwandveränderungen nach Behandlung mit Magnesiumorotat - Jellinek, Harry; Takács, Eva (Arzneimittelforschung, 2000)
Course of the Progression of Experimentally Induced Arteriosclerotic Vessel Wall Changes after Treatment with Magnesium OrotateThere are some experimental and clinical results regarding blood vessel protective properties of magnesium orotate (CAS 27067-77-2) till now. The goal of the present investigation was to verify the therapeutical efficacy of magnesium orotate vs. its singular components in cholesterol fed rabbits. Besides, the blood-lipid concentrations (LDL as risk factor for atherosclerosis and HDL as negative risk factor) were analyzed in relation to pathomorphological changes in the aortic blood vessel wall.The results of our experiments in New Zealand rabbits support the assumption that orotic acid and especially magnesium orotate influence the lipid level and/or the LDL/HDL-quotient in a favorable way and that they decrease the interaction between monocytes/macrophages and the endothelium of the blood vessels. Consequently, the plaque formation will be decreased in a clinically relevant manner.
Keywords: CAS 65-86-1; CAS 7786-30-3; CAS 27067-77-2; Hypercholesterolaemia; Magnesium orotate, effects on arteriosclerosis, rabbit